منهج الإمام النسائي في التفسير من خلال كتابه "السنن الكبرى": سورة البقرة أنموذجاً - Ili Dalila Binti Mohd Redzwan; Noor Mohammad Osmani (Universiti Sains Islam Malaysia, 2024)
Journal of Hadith Studies Volume 9 Issue 1 Page (167-187)